Answer:
Explanation:
Given: Circle O with BT as a tangent at point B.
T is the midpoint of arc CD.
To prove: (CA)(TB) = (TA)(CT)
Since point T is the midpoint of arc CD,
Therefore, m(arc CT) = m(arc TD)
and m∠CAT ≅ m∠DAT
m(∠ACT) = 90° [Angle subtended by the diameter]
By applying tangent rule in triangles ACT and ABT,
tan(∠CAT) =
![(CT)/(CA)](https://img.qammunity.org/2021/formulas/mathematics/high-school/lf31n99lotzhgzcuxwg53vz7nr6q76te37.png)
Similarly, tan(∠BAT) =
![(TB)/(TA)](https://img.qammunity.org/2021/formulas/mathematics/high-school/nkgl0olstpmnnz87u92tw4rnj92krkowlj.png)
Since tan(∠CAT) = tan(∠BAT)
Therefore,
![(CT)/(CA)=(TB)/(TA)](https://img.qammunity.org/2021/formulas/mathematics/high-school/h8ta0m2gceo0jln2cr5mnxdik3h2wxy6g8.png)
(CA) × (TB) = (CT) × (TA)
Hence proved.